(untitled) (Orinoquia, 2017)
Clustering methodology was used to group three neighborhoods in Quibdo taking into account factors that favor the development of malaria. The Kohonen self-organizing maps were used for the analysis of the most significant features in the standings. The detected clusters were compared with the geographical classification of houses, finding that the Kohonen self-organizing maps households classified by environmental conditions conducive to development rather than the administrative classification of the city.